A van der Waals DFT study of PtH2 systems absorbed on pristine and defective graphene - López Corral, Ignacio (2016)
We used a density functional that incorporates van der Waals interactions to study hydrogen adsorption onto Pt atoms attached to carbon-vacancies on graphene layers, considering molecular and dissociated hydrogen-platinum coordination structures. PtH2 complexes adsorbed on several sites of pristine graphene were also studied for comparison. Our results indicate that both a Kubas-type dihydrogen complex and a classic hydride without H-H bond are the preferential PtH2 systems on the vacancy site of graphene. In contrast, the Kubas complex is unstable onto pristine graphene and the hydride is obtained at all adsorption sites. Our simulations suggest that the C-vacancy decreases the reactivity of the metal decoration, allowing a non-dissociative hydrogen adsorption. The H2 molecule is oriented almost perpendicular to the outermost C-Pt bond, interacting also with the graphene surface through σ-H and π-C states. This stabilization of the Kubas-type complex could play a very important role for hydrogen storage in Pt-decorated carbon adsorbents with vacancies.